Spatial and Temporal Variation of Fish Assemblages in Seti Gandaki River, Tanahu, Nepal - PRASAD, ARCHANA; SHRESTHA, ANJANA; LIMBU, JASH HANG; SWAR, DEEP (Borneo Journal of Resource Science and Technology, 2020)
The space and time variations of the fish community structure in hill streams of Nepal are poorly understood. This research aims at studying the space and time variation of fish community structure in the Seti Gandaki River, Tanahu, Nepal. The field survey was conducted from July 2017 to June 2018 and the fishes were sampled from six sites using a medium size cast net of mesh size ranging from 3 mm to 6 mm mesh size, 25-33 feet length and 3.5-5 feet width, with the help of local fisher man. A total of 1,440 individuals were caught representing 46 species belonging to three order, nine families and 23 genera. The analysis of similarity (ANOSIM) showed significant difference in space (R = 0.824, P = 0.001) but not in time (R = 0.135, P = 0.021). On the basis of similarity percentage (SIMPER) analysis, 85.43% similarity was found among the seasons and major contributing species were Barilius bendelisis (8.44%) followed by B. vagra (7.79%), Tor putitora (7.27%), Garra gotyla (7%), Acanthocobotis botia (6.7%), Neolissochilus hexagonolepis (6.64%), Barilius shacra (6%), B. barila (4.5%) and Opsarius barna (4.37%). On the other hand, 85.24% similarity was found among the sites and major contributing species were B. bendelisis (8.8%) followed by B. vagra (7.6%), G. gotyla (7.27%), T. putitora (7.17%), A. botia (6.97%), N. hexagonolepis (6.7%), B. shacra (6.34%), B. barila (4.7%) and O. barna (4.39%). Results from the Canonical Correspondence Analysis indicated that the environmental variables, such as pH, total hardness, alkalinity, dissolved oxygen and water temperature have shown to determine the fish community structure of Seti Gandaki River. Keywords: Fish diversity, freshwater, habitat, spatio-temporal, stream